Peran Consumer Awareness dan Perception terhadap Buying Interest pada Properti Syariah - Fuji Safitri; Erry Sunarya; R. Deni Muhammad Danial (IPM2KPE, 2019)
The purpose of this study is to study the interaction of consumer awareness and perception of buying interests. The method in this study uses non propbability sampling, namely convenience sampling by distributing questionnaires to prospective sharia property buyers. The analysis technique used is multiple linear regression analysis, and for hypothesis testing is a statistical test simultaneously (F test). F test results show a sig value of 0,000 <0,05 which means that together Consumer Awareness (X1) and Perception (X2) have a significant effect on Buying Interests (Y). Based on the test of the coefficient of determination of 0.749 can be interpreted according to the contribution given Consumer awareness and Perception of Buying Interest is 74.9%, then by 25.1% can be changed by other variables that are not necessary in this study. Keywords : Consumer Awareness, Perception dan Buying Interest